FXR Friend-ChIPs in the Enterohepatic System - Meadows, Vik; Yang, Zhenning; Basaly, Veronia; Guo, Grace L. (Seminars in Liver Disease, 2023)
Chronic liver diseases encompass a wide spectrum of hepatic maladies that often result in cholestasis or altered bile acid secretion and regulation. Incidence and cost of care for many chronic liver diseases are rising in the United States with few Food and Drug Administration-approved drugs available for patient treatment. Farnesoid X receptor (FXR) is the master regulator of bile acid homeostasis with an important role in lipid and glucose metabolism and inflammation. FXR has served as an attractive target for management of cholestasis and fibrosis; however, global FXR agonism results in adverse effects in liver disease patients, severely affecting quality of life. In this review, we highlight seminal studies and recent updates on the FXR proteome and identify gaps in knowledge that are essential for tissue-specific FXR modulation. In conclusion, one of the greatest unmet needs in the field is understanding the underlying mechanism of intestinal versus hepatic FXR function.
Keywords: bile acids; farnesoid X receptor; proteome; tissue-specific FXR functions